Implementasi Teori Belajar Konstruktivisme bagi Pembelajaran Pendidikan Agama Kristen di Sekolah - Remegises Danial Yohanis Pandie; Yunardi Kristian Zega; Desetina Harefa; Stefanus Meo Nekin; Rini Sumanti Sapalakkai; Selvyen Sophia (REAL DIDACHE: Journal of Christian Education, 2022)
The implementation of teaching and learning activities becomes more effective if you pay attention to the use of learning theory in the classroom environment. However, the fact is that there are still some learning implementations that ignore this, so that learning outcomes are not in accordance with the achievement targets. One of the learning theories that is often used is constructivism learning theory. This learning theory gives students the freedom to build their own knowledge according to what is learned in the learning environment. The means of supporting the implementation of constructivism learning theory is technology. Technology makes it easy for educational practitioners to explore innovative patterns and materials to make an impact on students. Therefore, the purpose of writing this article is to explain the application of constructivism learning theory in Christian religious education in schools. The method in this research is a literature study method which refers to data or references related to the topic raised. Researchers collect various theories and information from library materials and conduct analytical studies of various written sources that can be justified academically. The results of this study are constructivism learning theory plays an important role in Christian religious education in schools, because it can provide space for students to easily learn by using technology, and make it easier for students to get opportunities to learn more independently.Keywords: Christian Religious Education; School; Technology; Constructivism Learning Theory Abstrak Pelaksanaan kegiatan belajar mengajar menjadi lebih efektif jika memperhatikan penggunaan teori belajar dalam lingkungan kelas. Namun, faktanya masih terdapat beberapa pelaksanaan belajar yang mengabaikan hal tersebut, sehingga hasil belajar tidak sesuai dengan target pencapaian. Salah satu teori belajar yang sering digunakan adalah teori belajar konstruktivisme. Teori belajar ini memberikan kebebasan kepada siswa untuk membangun pengetahuannya sendiri sesuai dengan apa yang dipelajari dalam lingkungan belajar. Sarana pendukung implementasi teori belajar konstruktivisme adalah teknologi. Teknologi memberikan kemudahan bagi praktisi pendidikan untuk mengeksplorasi pola dan materi yang inovatif agar memberikan dampak bagi siswa. Oleh sebab itu, tujuan dari penulisan artikel ini untuk menjelaskan tentang penerapan teori belajar konstruktivisme dalam pendidikan agama Kristen di sekolah. Metode dalam penelitian ini adalah metode studi pustaka yang mengacu pada data atau referensi yang berkaitan dengan topik yang diangkat. Peneliti mengumpulkan berbagai teori dan informasi dari bahan kepustakaan dan melakukan kajian analitis terhadap berbagai sumber tertulis yang dapat dipertanggungjawabkan secara akademik. Hasil dari penelitian ini adalah teori belajar konstruktivisme berperan penting dalam pendidikan agama Kristen di sekolah, karena dapat memberikan ruang kepada siswa untuk mudah belajar dengan menggunakan teknologi, serta memudahkan siswa untuk mendapatkan kesempatan belajar secara lebih mandiri. Kata Kunci: Pendidikan Agama Kristen; Sekolah; Teknologi; Teori Belajar Konstruktivisme